Uji Kadar Senyawa Flavonoid Dan Antioksidan Ekstrak Etanol Selada Air (Nasturtium Officinale R.Br) Menggunakan Metode Spektrofotometri Uv-Vis - Dewi Rahmayani; Diesna Sari; Fauziah (Nutrition Science and Health Research, 2023)
Selada air (Nasturtium Officinale R.Br) are widely found in Indonesia and have potential as antioxidants. The purpose of this study was to analyze the levels of flavonoids and antioxidant activity of Selada air extract. Selada air were extracted by maceration method with 70% ethanol as solvent. The flavonoid content of the extract was measured by the UV-Vis Spectrophotometry method, while the antioxidant activity of the extract was determined by the DPPH method. The results of this study indicate that the ethanol extract of the Selad air has a flavonoid content of 13,9 mgQE/g extract and the antioxidant activity of the compound obtained an IC50 value of 102,26 ppm with a moderate antioxidant category. Keywords: Antioxidant; DPPH, Flavonoids: Nasturtutium Officinale R.Br